Technology Roadmapping for Renewable Fuels: Case of Biobutanol in Brazil - Natalense,Julio (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2013)
Technology roadmapping has been used to define long term strategies and research agenda for the development of biofuels. The present work proposes the use of technology roadmapping as a technique for long term strategic planning of the biobutanol development, aligning long term goals with the resources, funding, and priorities to fulfill the needs in the development process in Brazil. Interviews have been used in the roadmapping process as an alternative to the workshops on market, product and technology. It allows the participation of companies in a highly competitive environment. The use of interviews allows the information to be collected individually, contributing to the elaboration of a roadmap. The results show that sugar cane has the potential to be used as a feedstock in the biobutanol production process, enabling Brazil to become a key exporter to supply other countries. For the short future, biobutanol has the potential to be produced in Brazil to replace petro-butanol as a solvent in industrial applications and to build the export platform for the fuels market .